Pengaruh Debt To Equity Ratio, Return On Equity, Pertumbuhan Perusahaan dan Ukuran Perusahaan Terhadap Nilai Perusahaan yang Terindek pada LQ-45 di Bursa Efek Indonesia - Dwi Rahayu; Sutikni Sutikni; Nur Endah Ratih U M (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research aims to examine the influence of Debt to Equity Ratio (DER), Return On Equity (ROE), company growth and company size on the value of companies indexed on LQ-45 on the Indonesia Stock Exchange in the 2020-2022 period. The sample in this study was 23 companies indexed on the LQ-45 which were selected using the purposive sampling method. Research data was obtained from the official website owned by Busa Efek Indonesia, the data was processed using the SPSS version 23.0 program, and analyzed using multiple linear regression. The research results show (1) Debt to Equity Ratio (DER) has a negative and insignificant effect on Company Value, as evidenced by the calculated t value being smaller than the t table, namely -1.022 < 1.668, with a significant value of 0.31 > 0.05. (2) Return On Equity (ROE) has a positive and significant effect on Company Value, as evidenced by the calculated t value being greater than the t table, namely 12.593 > 1.668, with a significant value of 0.00 < 0.05. (3) Company growth has a negative and significant effect on company value, as evidenced by the calculated t value being smaller than the t table, namely -2.861<1.668, with a significant value of 0.006<0.05. (4) Company size has a negative and insignificant effect on company value, as evidenced by the calculated t value being smaller than the t table, namely -1.233 < 1.668, with a significant value of 0.22 > 0.05.